ANTIMICROBIAL ACTIVITY OF IN VITRO AND IN VIVO PLANT EXTRACTS OF CEROPEGIA PUSILLA. WIGHT AND ARN AN ENDEMIC MEDICINAL PLANT - K.KALIMUTHU; R.PRABAKARAN; C. BRINDHA (International Journal of Pharma and Bio Sciences, 2013)
The present study aimed at to evaluate the antimicrobial activity of methanol extracts of the endemic medicinal plant, Ceropegia pusilla against five different bacterial strains namely, Shigella sonnei MTCC 2957, Klebsiella pneumoniae MTCC 109, Escherichia coli MTCC 118, Staphylococcus aureus ATCC 43300 and Bacillus sp., and four different fungal strains namely, Aspergillus sp., Mucor sp., Penicillium sp., and Candida albicans ATCC 60192, by agar well diffusion method. The methanol extract from the in vitro plant showed higher inhibitory effect towards the bacterium, Klebsiella sp., moderate inhibitory effect against the fungal strains Penicillium sp., and Candida albicans. There is no inhibitory effect towards the other bacterial and fungal strains whereas the extract from in vivo plant showed a higher inhibitory effect towards the bacterium Klebsiella sp., and fungal strains Mucor sp., Penicillium sp., and Candida albicans., moderate inhibitory effect against Staphylococcus sp., and no inhibitory effect against the other bacterial and fungal strains. On the basis of this experimental result, it can be concluded that methanol extract of in vitro and in vivo plants of Ceropegia pusilla could be considered for further isolation and evaluation as therapeutic antimicrobial.